A novel layer-structured PtN₂: first-principles calculations - Fan, C.Z.; Li, J.; Hu, M.; Zhao, Z.S.; Xu, B.; He, J.L. (Сверхтвердые материалы, 2013)
Platinum nitride as the first successfully synthesized noble metal nitride shows superior mechanical properties and exotic electronic structure that rival those of conventional transition metal nitrides. In the past diverse crystal structures have been proposed to understand its unusual properties. However, very few works pay attention to the dynamic stability of these phases. Here, we examine the potential structures of platinum nitride with a chemical composition of PtN₂ by utilizing a widely adopted evolutionary methodology for crystal structure prediction. Except reproducing the previously proposed phases, we also identify a Pmmm symmetric novel layer structure with a low formation enthalpy that is slightly lower than those of marcasite and CoSb₂ structures but slightly higher than that of pyrite structure. The elastic constants and the lattice dynamical calculations show that this layer-structured PtN₂ is mechanically and dynamically stable. The calculated band structures suggest this new phase together with the simple tetragonal phase are metallic, while other phases are insulators. In addition, it is found that the fluorite structure is dynamically unstable by the phonon spectrum calculations, although it is mechanically stable as suggested by calculated elastic constants. Розглянуто потенційні структури нітриду платини з хімічним складом PtN₂, використовуючи широко прийняту еволюційну методологію прогнозування кристалічних структур. Крім відтворення раніше запропонованих фаз, ідентифіковано нову симетричну шарувату структуру, просторова група Pmmm, з низькою ентальпією формування, яка трохи менша, ніж ентальпії структур марказиту і CoSb₂, але дещо більша, ніж ентальпія структури піриту. Постійні пружності і динамічні розрахунки решітки показують, що цей нітрид платини (PtN₂) з шаруватою структурою механічно і динамічно стабільний. Розраховані зонні структури дозволяють припустити, що ця нова фаза разом з простою тетрагональною фазою є металічною, тоді як інші фази є діелектричні. Розрахунками фононного спектру встановлено, що структура флюориту динамічно нестабільна, хоча механічно стабільна, як передбачається розрахованими константами пружності. Рассмотрены потенциальные структуры нитрида платины с химическим составом PtN₂, используя широко принятую эволюционную методологию прогнозирования кристаллических структур. Кроме воспроизведения ранее предложенных фаз, идентифировано новую симметричную слоистую структуру, пространственная группа Pmmm, с низкой энтальпией формирования, которая немного меньше, чем энтальпии структур марказита и CoSb₂, но немного больше, чем энтальпия структуры пирита. Постоянные упругости и динамические расчеты решетки показывают, что этот нитрид платины (PtN₂) со слоистой структурой механически и динамически стабилен. Рассчитанные зонные структуры позволяют предположить, что эта новая фаза вместе с простой тетрагональной фазой является металлической, тогда как другие фазы являются диэлектрическими. Расчетами фононного спектра установлено, что структура флюорита динамически нестабильна, хотя механически стабильна, как предполагается рассчитанными константами упругости.